Pemberdayaan Masyarakat Berbasis Komunitas Melalui Usaha Mikro Kecil Menengah (UMKM) (Studi Kasus Kelompok Pembuat Kritcu BaBe di Desa Batu Belubang) - Tiara Ramadhani (Prodi Sosiologi Universitas Mataram, 2020)
Indonesia as a Unitary State in realizing national goals regardless of ethnicity, race, and religion. This means that the national goal covers all Indonesian people without exception. So here the Government which is the organizer and mobilizer in realizing the national goals must play an active and sustainable role to carry out national development. The implementation of development in Indonesia is basically a process of humanizing people faced by a number of multidimensional challenges. One of them is the problem of poverty. poverty is a problem that is never resolved from time to time. The national development is realized through economic development, which not only focuses on the physical condition of a region, but the community can participate in a development process that can improve economic welfare through the process of community empowerment. One form of community empowerment is community empowerment in Batu Belubang Village, Bangka Tengah Regency, which is carried out through a community of kritcu makers (processed seafood typical of Bangka Belitung). It is said that community-based community empowerment is that people become independent and can improve economic well-being, especially the economic well-being of their families. The research method used in this research is qualitative research method. This research aims to gain a deep understanding of the phenomena that occur in society. As for the type of qualitative research in this research is a case study. Data sources come from housewives as MSMEs and batu belubang village officials and articles sourced from newspapers and scientific journals. The results showed that MSME products from Batu Belubang Village run well and develop rapidly, as seen from the turnover obtained every month by each member of the group.